Emergent Cervical Decompression in a Child with MURCS Association - Claude Abdallah; Leanne Foster (Global Journal of Anesthesiology - Peertechz Publications, 2016)
This case report describes an unusual presentation and anesthesia management of a rare genetic  association. The MURCS association, a variant of Mayer-Rokitansky-Küster-Hauser syndrome is a rare (1/4500-1/50,000) congenital syndrome, of unknown etiology, consisting of mullerian duct (MU) aplasia, renal (R) aplasia, and cervicothoracic somite (CS) dysplasia.